2010
DOI: 10.1007/s11517-010-0713-z
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral photoplethysmography variability analysis of sepsis patients

Abstract: Sepsis is associated with impairment in autonomic regulatory function. This work investigates the application of heart rate and photoplethysmogram (PPG) waveform variability analysis in differentiating two categories of sepsis, namely systemic inflammatory response syndrome (SIRS) and severe sepsis. Electrocardiogram-derived heart period (RRi) and PPG waveforms, measured from fingertips (Fin-PPG) and earlobes (Ear-PPG), of Emergency Department sepsis patients (n = 28) with different disease severity, were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 41 publications
2
41
1
Order By: Relevance
“…Apart from PPG signals being used in estimation of the SpO 2 values, these volumetric changes in the finger PPG signal appear as an information source for several indirect measurement methods [4,7,12]. In a previous study [6], a moderate correlation (r = 0.54) was found between fingertip PPG waveform variability (PPGV) and systemic vascular resistance (SVR).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from PPG signals being used in estimation of the SpO 2 values, these volumetric changes in the finger PPG signal appear as an information source for several indirect measurement methods [4,7,12]. In a previous study [6], a moderate correlation (r = 0.54) was found between fingertip PPG waveform variability (PPGV) and systemic vascular resistance (SVR).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have demonstrated clear links between PPGV and conditions associated with sympathetic changes [5,7,10,11,16,17,26], no study has ever been performed to establish a relationship between the spectral pattern of PPGV and a quantitative measure of vascular tone. In addition, since the suppression of sympathetic vascular tone could lead to a relative dominance of HF over LF power in PPGV [11,26], we also examined whether the PPGV spectral powers were useful for the categorical identification of patients in highly vasodilated states (indicated by the low SVR).…”
Section: Introductionmentioning
confidence: 99%
“…Infrared light can penetrate deep into the skin and subcutaneous tissue and is relatively insensitive to blood oxygenation [8,12], thus the resultant PPG signal reflects total blood volume change in the fingertip circulation, under the combined influences of central perfusion pressure and local sympathetic vascular control [2]. Similar to BPV, the frequency spectrum of PPG variability (PPGV) consists of both low frequency (LF) vasomotor waves, and high frequency (HF) respiratory fluctuations [5,10,11,16,17,23,26]. Sympathetic activation induced by active standing has been shown to augment normalized LF power of PPGV [5,17], whereas suppression of basal sympathetic tone by induction of anesthesia leads to a relative reduction in LF and enhancement of HF fluctuations [11,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular opinion is that the low-frequency oscillations in PPGV characterize sympathetic regulation of peripheral vessels tone [26][27][28]. However, it is important to consider that PPG signal contains information about both peripheral blood flow (including microcirculatory bloodstream) and distal arterial bed [29].…”
Section: Introductionmentioning
confidence: 99%